KAJIAN KEBERLANJUTAN PENGELOLAAN HUTAN MANGROVE DI MANGROVE CENTER GRAHA INDAH (MCGI) KOTA BALIKPAPAN PROVINSI KALIMANTAN TIMUR - Jaya, Eddy E (Program Studi Kesehatan dan Keselamatan Kerja, 2019)
The existence of mangrove forest resources at Graha Indah Mangrove Center (MCGI) in Balikpapan City certainly will not provide optimal value for benefits without sustainability in management. As For Objective of this study is to review and analyze mangrove management sustainability at Mangrove Center Graha Indah (MCGI) in Balikpapan. This study used quantitative positivist approach conducted longitudinally due to its sustainability nature. Study data is questionnaire scores distribution of sustainability dimension conducted by 25 judgment expert. Data analysis was done using Multidimensional Scaling (MDS) through Rap-Mangrove MCGI approach. Study result concluded that mangrove management at Mangrove Center Graha Indah (MCGI) in Balikpapan held the status quite sustainable (59,23) in multidimensional term. Meanwhile, all five dimension were also included in the status category of quite sustainable, those are ecology dimension (51,42), economy dimension (56,97), social cultural dimension (55,68), technology and information dimension (55,43), and legal and institutional dimension (61,83). Though this mangrove forest held the status quite sustainable, to improve its sustainability it is suggested to improve those sensitive attributes and particularly so that Local Government of Balikpapan should carry an active role by not only publishing regulation or provision related with management and conservation of mangrove in this region, but also in funding and strengthening institutional structure.